Supersymmetric gauge theories with decoupled operators and chiral ring stability - Benvenuti, S; Giacomelli, S (American Physical Society, 2017)
We propose a general way to complete supersymmetric theories with operators below the unitarity bound, adding gauge-singlet fields which enforce the decoupling of such operators. This makes it possible to perform all usual computations, and to compactify on a circle. We concentrate on a duality between an N = 1 SU(2) gauge theory and the N = 2 A3 Argyres-Douglas, mapping the moduli space and chiral ring of the completed N = 1 theory to those of the A3 model. We reduce the completed gauge theory to 3d, finding a 3d duality with N = 4 SQED with two flavors. The naive dimensional reduction is instead N = 2 SQED. Crucial is a concept of chiral ring stability, which modifies the superpotential and allows for a 3d emergent global symmetry.